Comparative transcriptome analysis of root types in salt tolerant and sensitive rice varieties in response to salinity stress. Issue 4 (22nd September 2021) - Cartagena, Joyce A.; Yao, Yao; Mitsuya, Shiro; Tsuge, Takashi
Abstract: Salinity tolerance in rice is a very important trait, especially in areas that are affected by soil salinity, such as tsunami‐devastated areas and coastal regions in rice‐producing countries. The roots are the key organs that first detect and respond to salinity stress; thus, it is important to have an understanding of how roots contribute to salinity tolerance in agricultural crops. After salinity treatment of the salt tolerant (Mulai) and sensitive (IR29) rice varieties, it appeared that among the three types of roots, the L‐type lateral roots (LLR) were the most sensitive to salinity stress in Mulai and the most tolerant in IR29. The nodal roots (NR) and the S‐type lateral roots (SLR) were all negatively affected by salinity treatment in both rice varieties. In order to elucidate the molecular mechanism of the difference in stress response among rice root types, the RNA‐seq transcriptome profiles of NR, LLR, and SLR were analyzed in Mulai and IR29. Between the two rice varieties, more transporters were found to participate in the regulation of salt tolerance in Mulai roots, such as those involved in ion and sugar transport. In IR29, many of the genes detected were associated with transcription regulation, including stress‐inducible genes such as NAC, WRKY and MYB . Among the different root types, gene expression in LLR and SLR were significantly regulated in both rice varieties. Taken together, the genes identified in this study may be utilized in the varietal improvement of rice with very specific root traits that can enhance tolerance to salinity stress.